Reliability analysis of load-sharing systems with spatial dependence and proximity effects. (May 2022) - Brown, Bodunrin; Liu, Bin; McIntyre, Stuart; Revie, Matthew
Abstract: In the operating process of multi-component systems, components may interact with each other in a way that the load of a failed component is taken up by its nearby components at varying proportions. As a result, the failure rates of the proximate components are accelerated while distant components are not affected. This paper develops a novel spatial model for estimating the reliability of a load-sharing system considering spatial dependence and proximity effects. The spatial model is applicable to systems with heterogeneous or homogeneous components and is suitable for systems with or without distance information. To investigate the importance and significance of the spatial effect, we compare our spatial model with an equal load-sharing through numerical examples. Our results demonstrate that our model is more accurate than standard load sharing models in evaluating system reliability when spatial effects exist. Highlights: Developed a load sharing model considering spatial dependency and proximity effect. Investigated the spatial effect on load distributions among components. Investigated the spatial effect when distance information is known and unknown. Compared our model with standard load sharing models. Demonstrated that spatial model is more accurate in presence of spatial effect.